2004
DOI: 10.1038/sj.ijir.3901219
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in men with obstructive sleep apnea syndrome: a randomized study of the efficacy of sildenafil and continuous positive airway pressure

Abstract: The aim of this study was to compare the efficacy of sildenafil and continuous positive airway pressure (CPAP) in men with erectile dysfunction (ED) and obstructive sleep apnea syndrome (OSAS). In all, 30 men were randomly treated for 12 weeks either with sildenafil 100 mg before intercourse (15 men) or CPAP during night time sleep (15 men). Under sildenafil, 97/180 (53.9%) of attempted intercourses were successful compared to 33/138 (23.9%) under CPAP. The mean IIEF (erectile function domain score) was 12.9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 24 publications
4
59
0
3
Order By: Relevance
“…20 Our findings of ED improvement with OSAS treatment are in concurrence with Karacan and Karatas', 13 which reported an improvement in a third of his patients with impaired NPT after a single night of CPAP treatment. Our findings are also in agreement with the recently published study by Perimenis et al 14 The primary outcome in their The most important finding of our study is that in 20% of patient's, long-term CPAP treatment alone helped to alleviate ED. Interestingly, the same efficacy rates were reported by Perimenis et al 14 When considering these results clinically, it becomes apparent that one of every five patients with OSAS and ED will respond to CPAP therapy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…20 Our findings of ED improvement with OSAS treatment are in concurrence with Karacan and Karatas', 13 which reported an improvement in a third of his patients with impaired NPT after a single night of CPAP treatment. Our findings are also in agreement with the recently published study by Perimenis et al 14 The primary outcome in their The most important finding of our study is that in 20% of patient's, long-term CPAP treatment alone helped to alleviate ED. Interestingly, the same efficacy rates were reported by Perimenis et al 14 When considering these results clinically, it becomes apparent that one of every five patients with OSAS and ED will respond to CPAP therapy.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are also in agreement with the recently published study by Perimenis et al 14 The primary outcome in their The most important finding of our study is that in 20% of patient's, long-term CPAP treatment alone helped to alleviate ED. Interestingly, the same efficacy rates were reported by Perimenis et al 14 When considering these results clinically, it becomes apparent that one of every five patients with OSAS and ED will respond to CPAP therapy. Owing to the apparently low response rate, the identification of clinically useful predictors of improvement is essential.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, RCTs comparing the effect of CPAP to sildenafil showed that both improved erectile function but sildenafil was superior. 147,[149][150][151] There are no RCTs that assessed the impact of CPAP on erectile dysfunction in patients with T2D but one uncontrolled study showed that CPAP for 3 months had no effect on sexual function in 35 men with T2D.…”
Section: Impact Of Continuous Positive Airway Pressurementioning
confidence: 99%
“…85 Other uncontrolled/observational studies suggested beneficial effects of CPAP on ED, and RCTs showed that sildenafil was superior to CPAP for managing ED. 84,[86][87][88] Impact of CPAP on glucose metabolism, CVD and QoL CPAP improved insulin sensitivity in patients with and without T2D in non-randomised trials 89,90 and in meta-analyses, 89,91,92 especially for patients using CPAP >4 hours/night. 93 Uncontrolled studies in patients with T2D89, [94][95][96][97] showed that CPAP improves postprandial hyperglycaemia, 94 glycaemic variability 95 and/or HbA1c .…”
Section: Osa Is Associated With Erectile Dysfunctionmentioning
confidence: 99%